TARGET balances: An anchor of stability - Marcel Fratzscher; Philipp König; Claudia Lambert (DIW Economic Bulletin, 2013)
The debate about TARGET2, the payment system of the European System of Central Banks (ESCB), has resulted in controversial discussions in Germany in recent years. The present study by DIW Berlin concludes that fears often expressed in this context of the risks to Germany are largely unfounded. Germany is - in contrast to what is often claimed - one the beneficiaries of the Target system. In particular, the fact that in the course of the crisis, financial risks could easily be reduced thanks to TARGET2 was beneficial for both the German government and private investors. Since the outbreak of the crisis, German investors pulled almost 400 billion euros from the crisis countries and they continue to hold around 740 billion in assets there.
Keywords: E44; E58; F34; G01; G15; 330; TARGET2; central bank liquidity; euro area crisis; capital flight